1992
DOI: 10.1099/00221287-138-12-2551
|View full text |Cite
|
Sign up to set email alerts
|

TPK gene products mediate cAMP-independent thermotolerance in Saccharomyces cerevisiae

Abstract: Incubation of Succharomyces cereuisiae with the plant cytokinin W-(A2-isopentenyl)adenine (2iP) resulted in an induction of thermotolerance similar to that induced by sublethal temperatures. Intracellular cAMP levels did not change significantly either during incubation at a sublethal temperature or in the presence of 2iP or ethanol. This suggested that stress-induced thermotolerance is triggered by a mechanism independent of cAMP activation. However, measurement of stress-induced thermotolerance in two mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Some workers have shown increased trehalose accumulation in the presence of CuSO 4 and CHX under special conditions, for example, after a longer incubation time or with different concentrations of the chemicals or different growth conditions [34, 40]. Similar to our data, Coote et al [42] showed that CHX did not lead to increase in trehalose level in growing cells. In another study [43], it was shown that a non‐lethal concentration of the chemical stressor called tetrachloroisophthalonitrile (TPN) led to induction of expression of stress proteins; however, trehalose level did not increase.…”
Section: Resultssupporting
confidence: 90%
“…Some workers have shown increased trehalose accumulation in the presence of CuSO 4 and CHX under special conditions, for example, after a longer incubation time or with different concentrations of the chemicals or different growth conditions [34, 40]. Similar to our data, Coote et al [42] showed that CHX did not lead to increase in trehalose level in growing cells. In another study [43], it was shown that a non‐lethal concentration of the chemical stressor called tetrachloroisophthalonitrile (TPN) led to induction of expression of stress proteins; however, trehalose level did not increase.…”
Section: Resultssupporting
confidence: 90%
“…In a first analysis of the signal transduction pathway that IS involved in the glucose-induced transcriptional activation of yeast rp-genes, we obtained evidence that cAMP does not act as the principal second messenger in this pathway [4] In these experiments we made use of the Icrl mu- Pka actwlty and with pkcl deletion strata DL376 (B) The growth medmm of DL376 was supplemented with 1 M sorbltol [6] tant [11], in which, due to a defect in the adenylate cyclase gene, the level of mtracellutar cAMP does not increase upon addition of glucose We extended these studies by investigating the nutritional response in a mutant lacking the regulatory subunIt Bcylp of protem kmase A (Pka) and hawng low constitutwe protein kinase A actwity due to deletions of the two catalytic subunit genes TPK2 and TPK3 and a TPK1 w mutation In the third [8] Consistent with recent findings of Struhl and Klein (12), no upshIft occurred in this mutant (Fig 2A) Apparently, control of Pka actwity, probably through Bcylp, Is a major determmant m the upshtft response, although not dependmg on the intracellular cAMP concentration Similar observations have been made for other processes, which are induced by glucose but nevertheless are also cAMP-independent, like activation of trehalase [13] or control of glycolytlc flux [14] In addition, actwatlon of Pka, independent of changes in cAMP levels, has been reported to occur after exposing yeast to heat shock [15] To our knowledge, our data are the first evidence that regulation of transcription, too, may be mediated through protein klnase A but in a cAMP-Independent fashion…”
Section: Protem Kmase a Actwtty Plays An Tmportant Role M Upshtft Regmentioning
confidence: 58%
“…5; Table I). The role of cytokinins in the acquisition of increased thermotolerance has been documented in a few plant systems such as tobacco leaves (Itai et al, 1978), maize seedlings (Caers et al, 1985), and potato tubers (Mauk and Langille, 1978), and in Saccharomyces cerevisiae (Coote et al, 1992). However, the data presented here provide evidence that levels of heat stress that disrupt maize kernel development also decrease endogenous cytokinin levels and that stem infusion of cytokinins during heat stress provides increased thermotolerance to developing maize kernels.…”
Section: Discussionmentioning
confidence: 99%